Effect of Na2CO3 on the preparation of metallic tin from cassiterite roasted under strong reductive atmosphere - Zhang, Yuanbo; Liu, Bingbing; Su, Zijian; Chen, Jun; Li, Guanghui; Jiang, Tao (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
Tin is an indispensable metal in the modern industry. The current tin smelting processes, however, have the disadvantages of high smelting temperature, long smelting time, especially high tin loss ratio (>10 wt%). The tin loss attributes to the volatilization as gaseous SnO and stannous silicate (SnO·SiO2) residual in the slag. An innovative approach for preparing metallic tin effectively from cassiterite in the presence of Na2CO3, named gas-based reduction roasting followed by water leaching process, is under development in Central South University, China. The present study, using chemically pure SnO2 and SiO2, aims to determine the impact of Na2CO3 on the metallic tin preparation from cassiterite by the novel process using XRD, SEM-EDS, chemical analysis, etc. It was found that Na2CO3 effectively restrained the tin volatilization as SnO and the formation of hardly reductive SnO·SiO2 during the reduction roasting process. In the presence of Na2CO3, most of SnO2 in the raw materials (mixture of SnO2+SiO2) was directly reduced to metallic tin, and part of SnO2 reacted with Na2CO3 to form intermediate Na2SnO3, which was then reduced to metallic tin. The SiO2 was transformed into Na2SiO3 and then went into the water solution in the following water-leaching process. The main reactions of the SnO2 + SiO2 system in the presence of Na2CO3 under reductive atmosphere were ascertained.